Tricky design the ethics of things - Fisher, Tom 1958-; Gamman, Lorraine (London, UK Bloomsbury Visual Arts, 2020)
"Tricky Things responds to the burgeoning of scholarly interest in the cultural meanings of objects, by addressing the moral complexity of certain designed objects and systems. The volume brings together leading international designers, scholars and critics to explore some of the ways in which the practice of design and its outcomes can have a dark side, even when the intention is to design for the public good. Considering a range of designed objects and relationships, including guns, eyewear, assisted suicide kits, anti-rape devices, passports and prisons, the contributors offer a view of design as both progressive and problematic, able to propose new material and human relationships, yet also constrained by social norms and ideology. This contradictory, tricky quality of design is explored in the editors' introduction, which positions the objects, systems, services and 'things' discussed in the book in relation to the idea of the trickster that occurs in anthropological literature, as well as in classical thought, discussing design interventions that have positive and negative ethical consequences"--Page 4 of cover.
List of illustrations -- Contributors -- Acknowledgements -- Foreword -- Introduction:ways of thinking tricky design -- Concealed trickery: design and the arms industry -- Designers and brokers of the mobility regime -- rickery in civic design: co-optation, subversion and politics -- Guns and morality: meditation, agency and responsibility -- The magic that is design -- Part 2 tricky processes, tricky principles -- Designer/shapeshifter: a decolonizing redirection for speculative and critical design -- Making "safety", making freedom: problem-setting, collaborative design and contested futures -- The nature of 'obligation' in doing design with communities: participation, politics and care -- Part 3 tricky policy -- Designing policy objects: anti-heroic design -- Tricky like a leprechaun' -- navigating the paradoxes of public service innovation the context of austerity -- Understanding suicide and assisted dying -- why is 'design for death' tricky? -- The quest for purity, ' clean' design and a new ethics of 'dirty design' -- Conclusion: design's tricky future.
Includes bibliographical references and index.
Keywords: Industrial design -- Moral and ethical aspects; Design -- Moral and ethical aspects; Material culture